The effect of 8 weeks IGF-1 injection and resistance training on Cox-2 and p53 expression in colorectal of male Wistar rats - babisan askari; nahid bijeh; amir rashidlamir (فیزیولوژی ورزش و فعالیت بدنی)
Abstract Purpose: The aim of this study was to determine the effect of 8 weeks IGF-1 injection and resistance training on Cox-2 and p53 expression in colorectal of male Wistar rats. Methods: A total of 28 male Wistar rats were randomly divided into 4 groups; saline injected control (Control), resistance training+saline injected (Training), resistance training+IGF-1 injected (Combined) and IGF-1 injected (Injection). Resistance training protocol consisted of climbing (three days/week, 5 reps/3 sets) a ladder carrying a load suspended from the tail for 8 weeks. IGF-1 and saline (1.5 µg/kg/day) were injected before and after exercise sessions. Three days after the last bout of exercise, colorectal tissues were collected and gene expression levels were analyzed using real-time PCR. Results: In Training, Combined and Injection groups, p53 expression in the colorectal decreased compared with Control (p